Performance evaluation of desilting basins of small hydropower projects. Issue 2 (3rd May 2016) - Singh, Gurdeep; Kumar, Arun
Abstract : There are many silt removing devices/methods used in small hydropower projects. Selection of these devices/methods depends upon the size and quantity of incoming sediments, land utilization for construction, size of sediment to be removed, and sequent of sediment flushing. The settling basin is the most widely used desilting device for small hydropower project (SHP). Vortex sediment settling basin developed recently is other cost-effective and efficient desilting device. This paper presents performance evaluation of settling basins and vortex sediment desilting devices constructed at SHP stations through field investigations at number of SHP stations in almost similar type of climatic and physiographic conditions. Silt removal efficiency has been compared using different methods for computing efficiency provided by different investigators. For SHP stations, efficient and economic desilting basin has been also suggested.